2011
DOI: 10.1039/c0cc02263b
|View full text |Cite
|
Sign up to set email alerts
|

Heteropoly acids as efficient acid catalysts in the one-step conversion of cellulose to sugar alcohols

Abstract: Cellulose and even spruce can be converted efficiently into valuable platform chemicals via combined hydrolysis and hydrogenation in the aqueous phase. Thereby, heteropoly acids together with supported ruthenium catalysts show not only high activity but also remarkable selectivity to sugar alcohols reaching up to 81% yield of C(4) to C(6) sugar alcohols in only 7 h at 160 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
144
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(150 citation statements)
references
References 36 publications
3
144
0
3
Order By: Relevance
“…In general, conversion of cellulose to polyols involves hydrolysis of cellulose to glucose over acids, 73 and subsequent hydrogenation of glucose to sorbitol and other polyols. [66][67][68][69][70][71]74 In our reaction, no acid is added or generated during the reaction, and therefore cellulose is not converted. Aer the reaction, cellulose and hemicellulose sediments can be separated out by magnetic ltering of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, conversion of cellulose to polyols involves hydrolysis of cellulose to glucose over acids, 73 and subsequent hydrogenation of glucose to sorbitol and other polyols. [66][67][68][69][70][71]74 In our reaction, no acid is added or generated during the reaction, and therefore cellulose is not converted. Aer the reaction, cellulose and hemicellulose sediments can be separated out by magnetic ltering of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…† For CD 3 Several studies have reported concurrent hydrogenation of cellulose and hemicellulose into alcohols. [66][67][68][69][70][71] We tested cellulose transformation under the same conditions as LDP. The reaction mixture is analyzed by HPLC.…”
Section: Resultsmentioning
confidence: 99%
“…Direct conversion of cellulose into sorbitol by hydrogenolysis has been achieved using supported platinum catalysts 6),7),11),29),30) and supported ruthenium catalysts 8),11),13),29),31), 32) . Removal of lignin and hemicellulose by chemical treatment is required to obtain pure cellulose from lignocellulosic biomass.…”
Section: Resultsmentioning
confidence: 99%
“…Noted that the presented yields in the case of recycling experiments were based on the freshly added substrate to allow comparability with reference experiments (88).…”
Section: Hydrolysis Reactionsmentioning
confidence: 99%